Translating the Immunobiology of SBRT to Novel Therapeutic Combinations for Advanced Prostate Cancer - Adorno Febles, Victor R.; Blacksburg, Seth; Haas, Jonathan A.; Wise, David R. (Frontiers in Oncology, 2020)
Stereotactic body radiotherapy is an increasingly used radiation modality for the treatment of both localized and metastatic prostate cancer. Substantial data suggests that prostate cancer may be more sensitive to higher doses of radiation per fraction due to its low α/β ratio. This increased sensitivity raises important questions as to how SBRT should be combined with systemic therapy for clinically significant prostate cancer, including whether androgen deprivation therapy retains its beneficial effects when combined with SBRT. Furthermore, pre-clinical and clinical data suggest pronounced immunomodulatory effects of SBRT, including observed improvements in T cell priming and trafficking. These data support investigational strategies combining SBRT with immunotherapy. Here we aim to review the data for the use of SBRT in both the local and metastatic disease settings as well as ongoing translational and clinical research examining combinations with ADT, immunotherapy and other targeted agents.